Career choices and career mobility of chinese pharmacy graduates: a cross-sectional study - Hongyu Gong; Yan Li; Wenyue Duan; Ying Chen; Jianyu Zhou; Shuming Cao (BMC Medical Education)
Abstract Background This study investigates the career mobility and employment status of Chinese pharmacy graduates, aiming to address workforce challenges and career planning within the pharmacy profession. Given the rapid expansion of the healthcare sector in China, understanding factors influencing job changes and career decisions is crucial for ensuring workforce stability and professional development. The study covers pharmacy graduates enrolled at Kunming Medical University from 1996 to 2012. Methods A cross-sectional online survey collected data from 231 respondents in April 2022, focusing on demographic characteristics, career choices, job changes, and the factors influencing these decisions. Multivariate logistic regression and Chi-square (χ²) tests were used to analyze the data, with a particular focus on the pharmacy practice, pharmaceutical sciences, and clinical pharmacy. Results Of the 231 respondents, 52.4% (n = 121) had never changed jobs, and 32.5% (n = 75) had changed jobs once or twice. The majority preferred working in governmental institutions (n = 146, 63.2%), with fewer graduates choosing domestic (n = 48, 20.8%) or overseas pharmacy enterprises (n = 20, 8.7%). Income and personal growth were significant factors influencing job changes (p < 0.05). Respondents who had changed jobs three or more times placed a greater emphasis on personal growth (Relative Risk Ratio [RRR]: 2.96; 95% Confidence Interval [CI]: [1.6, 5.49]). Conclusions This study reveals significant variations in job mobility and career choices among Chinese pharmacy graduates. Graduates in governmental institutions showed lower mobility, while those in pharmacy enterprises and non-pharmaceutical sectors experienced higher job changes. Income, personal growth, and work environment were key factors.